Translation and Decoloniality in Latin America - Fleck, Gilmei Francisco (2023)
Along this text we reflect about the content of concepts such as coloniality, decolonization and decoloniality (DUSSEL, 1942, MINGNOLO 2017; CASTRO GÓMEZ; GROSFOGEL, 2007) and their transit along the History of America. In this context we highlight the relevance that the knowledge of different languages developed since de beginning of the colonization (PAGANO, 2000). The impact of the interpreting services offered to the European by bilingual informants during the process of the “conquest” of America and the consequences of such actions to the native communities (DEL POZO GONZÁLEZ, 2017) are shown by us along this article. We also point out the fact of the election taken to translate in Latin America the European models of literary works – as sources that could feed their newborn literary polysystems (EVEN-ZOHAR, 1990). This action gave sequence to the cultivation of European ideologies, traditions, habits, and customs in American territories. The different political systems adopted in the postcolonial Latin America were also sorts of barriers to a decolonial translation practice, causing mutual unknowing among these countries. Such reasons lead us to defend the need of a decolonial translation practice in the academic environment, so that the decolonization of minds, identities, and the imaginary of Latin America can finally take place. Examples of such actions of decolonial translations (SALES SALVADOR, SPIVAK, 2006; VENUTI, 1995) are finally shown by us at the last part of this text, that start with a bibliographic revision about the main concepts and focus on our own translations practice.